2020
DOI: 10.1093/humrep/deaa214
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of nitrous dioxide are associated with lower AMH levels: a real-world analysis

Abstract: STUDY QUESTION Are there any associations between environmental pollutants and ovarian reserve, expressed by anti-Mullerian hormone (AMH) serum levels? SUMMARY ANSWER In this first real-world approach to demonstrate the relationship between air pollutants and serum AMH levels, adverse associations were observed for nitrogen dioxide (NO2) but not with particulate matter. WHAT I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…First, the follicular fluid is a distinct biological fluid from blood and may represent a more toxicologically relevant biofluid for investigating the impacts of air pollution on ovarian function. ( Qasemi and Amidi, 2020 ) Second, NO 2 exposure may have a specific negative impact on the ovary, ( Gregoire et al, 2021 ; La Marca et al, 2020 2020) which may be better captured by studying follicular fluid as opposed to blood.…”
Section: Discussionmentioning
confidence: 99%
“…First, the follicular fluid is a distinct biological fluid from blood and may represent a more toxicologically relevant biofluid for investigating the impacts of air pollution on ovarian function. ( Qasemi and Amidi, 2020 ) Second, NO 2 exposure may have a specific negative impact on the ovary, ( Gregoire et al, 2021 ; La Marca et al, 2020 2020) which may be better captured by studying follicular fluid as opposed to blood.…”
Section: Discussionmentioning
confidence: 99%
“…So far, two studies reported inconsistent results for the association of PM with AMH. 12,14 Such inconsistency may be due to differences in the study population, exposure levels and time windows of exposures examined, and geographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…So far, two studies reported inconsistent results for the association of PM with AMH. 12,14 Such inconsistency may be due to differences in the study population, exposure levels and time windows of exposures examined, and geographic characteristics. The observed associations in the main analysis were found in women above age 40, while there was less evidence of associations among younger women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The team found that AMH levels were lower in women who lived in areas with higher levels of pollution as assessed by measuring the daily values of fine particles (PM 2.5 and PM 10). When the team divided air pollution into four brackets, they found that three times as many women living in the lower bracket had lower levels of AMH than those in the higher brackets, referring to a level below 1 ng/mL, a value that correlates with a serious ovarian deficiency [122] (Figure 2).…”
Section: Environmental Pollutionmentioning
confidence: 99%